Explanation of Al-Kafiya by the Scholar Jalal Al-Din Muhammad bin Yusuf Al-Halawi Al-Sarai Al-Tabrizi (d. 838 AH):The Absolute Object as a model Study and Investigation - Muhammad Ismail al-Bayati, Monther Khader; Bahloul Al-Jubouri, Nafeh Alwan; Aliwi Al-Jubouri, Muwafaq Hussain (Journal of Tikrit University for Humanities, 2024)
As we know that Ibn al-Hajib (d. 646 AH) - may Allah have mercy on him - wrote a brief book on grammar in the middle of the seventh century AH, which needed explanation and facilitation, so those with knowledge poured in to explain it and facilitate it for the learners. However, Al-Halawi’s explanation was characterized by an abundance of reasoning and grammatical assumptions. Among the things that have benefited us from him is his brilliant book Sharh Al-Kafiya fi Al- Nahw, its sober expressions, its concise words, and its invaluable investigations. Scholars have dealt with it, studied it, and he was one of those who opened its closed chapters and paved the way for every student of the sciences with a sound understanding. The Imam, the scholar Jalal al-Din Muhammad ibn Yusuf al-Halawi al-Tabrizi, was unique in his style. He solved the words, smoothed out the expressions, opened the closed ones, and investigated the issues. He corrected, weighted, expressed, and clarified them. It was like a garden that gathered many colors, and it surpassed others in simplifying its essence, and it was unique. With a deep look, and the clarity of the idea, so he made the meanings clearer, and revealed the hidden phrases and structures that are difficult for the student to understand, and their awareness and perception are distorted by him, and explained the examples and evidence in it, and the most beautiful meanings, and mentioned the parsing of the ambiguous ones, so his explanation was the subject of our study and we paid all our attention to it until it came out easy and useful.